Adults Undergoing Allogeneic Bone Marrow Transplantation: Long-Term Follow-up of Secondary Malignancies - Muhammad Kamran Akbar, Aatika Habib , Humayun Mumtaz , Muhammad Arshad , Hefsa Qamar (Drugs and Cell Therapies in Hematology, 2021)
Objective: The goal of this study was to evaluate the predicted risk of secondary malignancies following allogeneic bone marrow transplantation (BMT) in a cohort of adult patients aged 18 years or older. Method: Between June 2016 and November 2020, a total of 44 patients over the age of 18 received allogeneic BMT. The diagnosis of secondary malignancy was confirmed through histologic examination. Independent t test and chi square analysis was used to discover the factors that contributed to the development of secondary malignancies. Six individuals in this group acquired a second malignancy on average 3 years following their transplant. Results: According to the results of the study, the cumulative incidence of future cancer was predicted to be 13.6 percent three years after transplantation, according to the research. When new cancer diagnoses were compared to those expected in the general population, the estimated observed/expected ratio of cancer diagnoses was 5.13. According to the results of the independent t and chi squrare analysis, the only significant predictor of secondary cancer development was the patient's age at the time of transplantation (P=0.01). Nonmelanomatous skin cancers and squamous cell tumours of the buccal cavity were the most frequently seen malignancies. Following allogeneic bone marrow transplantation, the chance of acquiring a subsequent cancer is significant, particularly in the elderly. Conclusion: The skin and mouth of long-term transplant recipients must be regularly monitored for early indications of malignancy, which are particularly common in skin and mouth cancer.